2020
DOI: 10.1155/2020/4545063
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Properties of SBS/Rice Husk Ash‐Modified Asphalt Binder and Mixture

Abstract: Sustainable materials in the field of road pavement have become a research direction in recent years. In this study, the rice husk ash with small dosage of styrene-butadiene-styrene (SBS) was added as a bioadditive into the base asphalt to modify its properties. Different contents (0, 2, 5, 10, and 15%) of rice husk ash (RHA) and 1% of SBS were selected to prepare the modified asphalt. Penetration, softening point, ductility, rotational viscosity test, and temperature sweep test were conducted to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…In summary, a similar analysis of biochar and other biomass carbon material has been reported by other researchers in terms of the high- and low-temperature performance. Previous studies revealed that biochar with a porous fibrous structure can enhance the high-temperature performance of asphalt [ 24 , 25 ], which would slightly impair the low-temperature performance [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, a similar analysis of biochar and other biomass carbon material has been reported by other researchers in terms of the high- and low-temperature performance. Previous studies revealed that biochar with a porous fibrous structure can enhance the high-temperature performance of asphalt [ 24 , 25 ], which would slightly impair the low-temperature performance [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…RHA and matrix asphalt can form a stable three-dimensional network system, which is conducive to improving the high-temperature deformation resistance and bonding properties of asphalt. Lu et al [ 15 ] selected different contents of RHA and 1% SBS to prepare modified asphalt and conducted a series of macro tests on asphalt and asphalt mixture. The results showed that the high-temperature performance of the RHA and SBS composite-modified asphalt mixture was better, and the water stability and low-temperature performance were slightly lower, compared with the matrix asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…Al estudiar al ligante asfáltico con base de penetración 70 y al bioasfalto con 2, 5, 10 y 15% de ceniza de cáscara de arroz más 1% de estireno-butadieno-estireno, pues se obtuvo que el aditivo mejoró el punto de reblandecimiento de la ligante virgen de 48.2 °C, aumentando un 4.7%, 6.0%, 8.3% y 9.3% respectivamente, mejorando la capacidad a la deformación a altas temperaturas [73].…”
Section: Punto De Reblandecimientounclassified
“…The studies conducted so far [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] have revealed that bio-ash considerably varies as to its composition and properties, depending on the origin of the biomass, biomass handling, and the combustion technology and temperature. The wide range of compositions and properties of bio-ash requires the testing of individual sources with the purpose of determining the possibility of using bio-ash in road construction as a substitute for traditional materials.…”
Section: Introductionmentioning
confidence: 99%